2019
DOI: 10.3928/01477447-20181206-04
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Augmentation With Absorbable Alginate Sheet Enhances Healing of the Rotator Cuff

Abstract: For anatomical restoration of a repaired rotator cuff, mechanical augmentation of the repaired structure is essential. Using histological and biomechanical evaluation in a rat model, the authors sought to determine the efficacy of an absorbable alginate sheet at the supraspinatus tendon-to-bone repair site for healing of the rotator cuff tear. Forty adult (12 weeks old) male Sprague– Dawley wild-type rats were used in this study. The animals were randomly separated into 2 groups: group 1, conventional supraspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…6 Mos. Harada, Y 2017 [ 70 ] Japan Rat (Mean weight 250g, 12 WKS) Self-con 30/30 IS Acute tear (full thickness) 1 WKS 8 WKS Hee, C. K 2011 [ 71 ] USA Ovine (F, 65–105 kg, 3.5+Years) Self-con 60/60 IS Acute tear (full thickness) 12 WKS 12 WKS Huang, C 2020 [ 22 ] China Rabbit/NZW (F, 2.8–3.5 kg, Adult) Ran 18/18 SS Acute tear (full thickness) 4, 8, 12 WKS 4, 8, 12 WKS Huang, C 2020 [ 72 ] China Rabbit/NZW (2.8–3.5 kg, Adult) Self-con 24/24 SS Acute tear (full thickness) 4, 8 WKS 4, 8 WKS Kim, D. H 2019 [ 73 ] Korea Rat/SD (M, 300–350 g, 12 WKS) Ran 20/20 SS Acute tear (full thickness) 6, 12 WKS 6, 12 WKS Kim, S. Y 2014 [ 74 ] Korea Rat/SD (M, 410–500 g, Adult) Ran 19/19 SS Acute tear (full thickness) 1, 2, 4, 8 WKS 2, 4, 8...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Mos. Harada, Y 2017 [ 70 ] Japan Rat (Mean weight 250g, 12 WKS) Self-con 30/30 IS Acute tear (full thickness) 1 WKS 8 WKS Hee, C. K 2011 [ 71 ] USA Ovine (F, 65–105 kg, 3.5+Years) Self-con 60/60 IS Acute tear (full thickness) 12 WKS 12 WKS Huang, C 2020 [ 22 ] China Rabbit/NZW (F, 2.8–3.5 kg, Adult) Ran 18/18 SS Acute tear (full thickness) 4, 8, 12 WKS 4, 8, 12 WKS Huang, C 2020 [ 72 ] China Rabbit/NZW (2.8–3.5 kg, Adult) Self-con 24/24 SS Acute tear (full thickness) 4, 8 WKS 4, 8 WKS Kim, D. H 2019 [ 73 ] Korea Rat/SD (M, 300–350 g, 12 WKS) Ran 20/20 SS Acute tear (full thickness) 6, 12 WKS 6, 12 WKS Kim, S. Y 2014 [ 74 ] Korea Rat/SD (M, 410–500 g, Adult) Ran 19/19 SS Acute tear (full thickness) 1, 2, 4, 8 WKS 2, 4, 8...…”
Section: Resultsmentioning
confidence: 99%
“…Nuss, C. A [ 89 ] found that the results of Poly-N-acetyl Glucosamine (sNAG) were superior to those of simple suture. One study [ 73 ] demonstrated that alginate scaffolds had better results than simple suture. Lopitz, Y [ 78 ] found that alginate-chitin combined with recombinant human bone morphogenetic protein-2 (rhBMP-2) had better results than bare scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the total score for a given slide could vary between 0 (a ruptured tendon) and 18 (most marked regeneration). 9 To eliminate observer error, a pathologist with at least 10 years of experience examined all slides in a randomized, blinded fashion 3 times at the same position and area of rotator cuff tissue using a microscope (Leica DM IL LED, Leica Microsystems, Wetzlar, Germany) and image system (LAS V4.8, Leica Microsystems, Wetzlar, Germany) at ×50 magnification. 40…”
Section: Methodsmentioning
confidence: 99%
“…7,8 However, natural polymers used to enhance rotator cuff healing have advantages in biocompatibility and biodegradability but often may not provide sufficient strength to serve as supports. 911…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation